When do politicians appeal broadly? The economic consequences of electoral rules in Brazil - Chin, Moya (American Economic Journal: Applied Economies)
Electoral rules determine how voters' preferences are aggregated and translated into political representation. Using a regression discontinuity design, I contrast single- and two-round elections in Brazil. In two-round elections, the eventual winner must obtain at least 50 percent of the vote. I show that two-round elections provide incentives for candidates to secure a broader base of support and provide public goods more broadly. Candidates represent a more geographically diverse group of voters, public schools have more resources, and there is less variation in resources across schools. Effects appear to be driven by strategic responses of candidates rather than differential entry into races.- Reproduced